Hubungan Tingkat Pengetahuan Perawat Tentang Standar Asuhan Keperawatan dengan Kelengkapan Dokumentasi Asuhan Keperawatan di Puskesmas Korleko - Hartini, Hartini; Menap, Menap; Taufandas, Maruli (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Nurses’ knowledge of nursing care standards is crucial to ensure the completeness of nursing care documentation. Complete and accurate documentation is an indicator of the quality of nursing services and patient safety. The aim of this study is to analyze the relationship between the level of nurses' knowledge about nursing care standards and the completeness of nursing care documentation at Puskesmas Korleko. This study uses an observational analytic design with a cross-sectional approach. The subjects of the study consisted of 33 nurses working at Puskesmas Korleko. Data collection was carried out through a questionnaire to measure the level of knowledge and a checklist to assess the completeness of documentation. Data analysis was conducted using the Spearman Rank correlation test to determine the relationship between variables. The results of the study showed that (1) 97% of nurses had good knowledge of nursing care standards, and 91% of them had very complete documentation; (2) a significant relationship between the level of nurses' knowledge and the completeness of documentation (correlation coefficient: -0.559, p-value: 0.001).